Impact of skeletal muscle measurements by chest computed tomography on survival and postoperative complications in patients with soft tissue sarcoma - ARIKAN, RUKİYE; EROL, BÜLENT; KÖSTEK, OSMAN; BAYOĞLU, İBRAHİM VEDAT; DANE, FAYSAL; YUMUK, PERRAN FULDEN; ÖZGEN, ZERRİN; BUĞDAYCI, ONUR (My University, 2022)
© 2022 Taylor & Francis Group, LLC.This study aims to evaluate whether sarcopenia, measured by chest computed tomography (CT), affects survival outcomes and postoperative complications in soft tissue sarcoma (STS) patients undergoing surgery. In this retrospective study, CT scans of 79 patients were reviewed to measure pectoralis and T12 vertebra muscle area. Both were then adjusted for height (cm2/m2) as pectoralis muscle index (PMI) and T12 vertebra muscle index (TMI). Analyses were performed by dichotomizing muscle indices at gender-specific 50th percentile; PMI and TMI < 50th percentile were defined as low, and ≥50th percentile as high. Overall postsurgical complication rate (PCR) was 16%. Median length of hospital stay (LOHS) was 10 days (3–90). PMI and TMI were significantly lower in women (p = 0.02, p = 0.04). Median body mass index was significantly higher in high PMI and TMI groups (p = 0.01 for both). PCR and LOHS were similar between low and high PMI and TMI groups. Median follow-up was 29 months, 37 patients had recurrence and 23 died. No significant difference was noted between low and high PMI and TMI groups, in terms of disease-free or overall survival. PMI and TMI as measured by chest CT had no impact on survival outcomes or postoperative complications in localized STS.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; Nutrition and Dietetics; Agricultural Sciences; Agriculture; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); BESLENME VE DİYETETİK; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); NUTRITION & DIETETICS; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE)